Implementasi Nilai-nilai Pancasila dalam Pembentukan Hukum Adat di Indonesia : Sebuah Tinjauan Filosofis dan Sosiologis - Ahmad Muhamad Mustain Nasoha; Ashfiya Nur Atqiya; Suci Wibowo; Annisa Ulfarisah; Mutya Suha Nugroho (Lembaga Pengembangan Kinerja Dosen, 2024)
This research discusses Pancasila values ​​in the formation of customary law through philosophical and sociological approaches. Pancasila as the basis of the state has an influence in the formation of national law, but its relationship with customary law, traditions and local norms requires further adjustments. This philosophical approach emphasizes the values ​​of Pancasila, such as Belief in One Almighty God, Just and Civilized Humanity, and Social Justice. This is different from sociological research that examines the response of indigenous communities to the function of Pancasila and the dynamics of social adaptation that occur. This research also provides scientific participation in understanding between national and local legal systems, and also provides a basis for legal policy regarding the dynamics of Indonesian socio-culture.